Analysis of cyclic phase transformations during additive manufacturing of hardenable tool steel by in-situ X-ray diffraction experiments. (1st March 2020) - Epp, Jeremy; Dong, Juan; Meyer, Heiner; Bohlen, Annika
Abstract: In-situ X-ray diffraction experiments were performed during Laser Metal Deposition of steel X40CrMoV5-1 at the Deutsches Elektronen-Synchrotron (DESY). The measurements were performed with monochromatic high-energy X-ray radiation in transmission, while full diffraction rings were recorded at 10 Hz. The first generated layer is remelted until deposition of the third layer on top, while partial re-austenitizing of the first layer occurs until deposition of the 7th layer. Self-tempering effects were analyzed based on martensite tetragonality. Strong decrease of carbon content in solution in martensite occurs during the deposition of the first five layers, resulting in low local hardness. Graphical abstract: Image, graphical abstract